When Women Held the Dragon's Tongue : and Other Essays in Historical Anthropology. - Rebel, Hermann (Berghahn Books, Inc., 2010)
"Peasants tell tales," one prominent cultural historian tells us (Robert Darnton). Scholars must then determine and analyze what it is they are saying and whether or not to incorporate such tellings into their histories and ethnographies. Challenging the dominant culturalist approach associated with Clifford Geertz and Marshall Sahlins among others, this book presents a critical rethinking of the philosophical anthropologies found in specific histories and ethnographies and thereby bridges the current gap between approaches to studies of peasant society and popular culture. In challenging the.
Keywords: Ethnohistory.; Philosophical anthropology.; Peasants.; Fairy tales.